The Analysis of King Caspian X’s Struggle to Find His Father’s Seven Best Friends in the Series Novel “The Chronicles of Narnia: The Voyage of The Dawn Treader” By C.S Lewis” - Dhafin Rozaq Azka; Saptanto Hari Wibawa; Samsul Hadi (Jurnal Penelitian Pendidikan, 2021)
Struggle is one of the values that can be included in literary works. This paper aims to analyze the struggle that is presented in the series novel The Chronicles of Narnia: The Voyage of the Dawn Treader. This is descriptive qualitative research. The data was taken from monologue and dialogue in the novel itself. To collect the data, the researcher used document analysis by Bowen. The researcher used theory from Milles and Huberman for analyzing the data. The results of struggle as extrinsic element there are three kinds of struggle: 1) against the time, this struggle emphasized how the character’s patience with the process and how to adapt to new circumstances; 2) against the outside factor, this struggle emphasized teamwork, faith, and not despair; 3) self-thought, this struggle emphasized how dealing with own mind can ruin our-self.